2022
DOI: 10.1177/10547738221097241
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Efficiency of Breathing Exercises via Telemedicine in Post-Covid-19 Patients: Randomized Controlled Study

Abstract: The aim of the study was to evaluate the effectiveness of breathing exercises given by telemedicine in post-Covid-19 dyspneic individuals. Individuals in the intervention group ( n: 26) were asked to perform breathing exercise three times a day for 5 weeks (one session performed via telemedicine each week). Individuals in the control group ( n: 26) were given a brochure explaining the exercises. The St George’s Respiratory Questionnaire, Pulmonary function tests, and six-minute-walk-tests were administered to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
78
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(78 citation statements)
references
References 35 publications
(39 reference statements)
0
78
0
Order By: Relevance
“…The pulmonary symptom scores in our study using the CAT demonstrated a statistically significant reduction during the course of the study, which was consistent with prior studies that have demonstrated that pulmonary exercises are effective in improving quality of life and pulmonary symptom scores in patients with COPD, asthma, bronchiectasis, and restrictive lung diseases (Essam et al, 2022; Pehlivan et al, 2019; Renolleau-Courtois et al, 2014; Tarigan et al, 2020). Recently, a 5-week, randomized controlled study of 52 individuals with post-COVID-19-related dyspnea who received a respiratory exercise breathing program via tele-medicine reported significantly improved quality of life scores in those individuals who were in the intervention group (Okan et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The pulmonary symptom scores in our study using the CAT demonstrated a statistically significant reduction during the course of the study, which was consistent with prior studies that have demonstrated that pulmonary exercises are effective in improving quality of life and pulmonary symptom scores in patients with COPD, asthma, bronchiectasis, and restrictive lung diseases (Essam et al, 2022; Pehlivan et al, 2019; Renolleau-Courtois et al, 2014; Tarigan et al, 2020). Recently, a 5-week, randomized controlled study of 52 individuals with post-COVID-19-related dyspnea who received a respiratory exercise breathing program via tele-medicine reported significantly improved quality of life scores in those individuals who were in the intervention group (Okan et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Five trials 21,24,25,27,29 reported treatment outcomes on overall quality of life among 366 participants 2). Figure 3 and eFigure 8 and eFigure 9 in Supplement 1 display the association of rehabilitation interventions with physical and mental health separately.…”
Section: Quality Of Lifementioning
confidence: 99%
“…Effects of treatment for persisting respiratory symptoms have been investigated in several studies. A combination of different breathing exercises for 5 weeks has been found to improve pulmonary function, quality of life and exercise capacity of patients with respiratory symptoms following COVID‐19 [93]. A breathing and wellbeing program including singing techniques had minor effects on breathlessness [94].…”
Section: Managementmentioning
confidence: 99%